2018
DOI: 10.1016/j.sjbs.2016.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Life forms, leaf size spectra, regeneration capacity and diversity of plant species grown in the Thandiani forests, district Abbottabad, Khyber Pakhtunkhwa, Pakistan

Abstract: The life form and leaf size spectra of plant species of the Thandiani forests, district Abbottabad, were studied during the summer of 2013. These forests host 252 plant species of 97 families. Biological spectra showed that Hemicryptophytes (80 spp., 31.74%) were dominant followed by Megaphanerophytes (51 spp., 20.24%), Therophytes (49 spp., 19.44%) and Nanophanerophytes (45 spp., 17.86). Hemicryptophytes are the indicators of cold temperate vegetation. At the lower elevations, Megaphanerophytes and Nanophaner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 9 publications
7
23
0
Order By: Relevance
“…Ali et al (2016) also reported mesophylls as the dominant leaf type in the Chail valley, Pakistan. The observed relationship between small leaves and cold or hot desert climates is explainable as an adaptive strategy for retaining soil moisture (Khan et al 2018). Our findings are comparable with those of Qadir and Tareen (1987), Greller (1988), Malik et al (2007), Asim et al (2016) and Haq et al (2018) who reported the dominance of similar leaf size spectra in their study areas.…”
Section: Leaf Size Spectrasupporting
confidence: 91%
See 2 more Smart Citations
“…Ali et al (2016) also reported mesophylls as the dominant leaf type in the Chail valley, Pakistan. The observed relationship between small leaves and cold or hot desert climates is explainable as an adaptive strategy for retaining soil moisture (Khan et al 2018). Our findings are comparable with those of Qadir and Tareen (1987), Greller (1988), Malik et al (2007), Asim et al (2016) and Haq et al (2018) who reported the dominance of similar leaf size spectra in their study areas.…”
Section: Leaf Size Spectrasupporting
confidence: 91%
“…Our floristic analysis showed that species with mesophylls dominated, followed by microphyll and nanophyll in the studied area. A high percentage of microphylls is typical for temperate climatic conditions (Khan et al 2018). Ali et al (2016) also reported mesophylls as the dominant leaf type in the Chail valley, Pakistan.…”
Section: Leaf Size Spectramentioning
confidence: 98%
See 1 more Smart Citation
“…Plant species distribution pattern and composition changes along various environmental factors in a gradual manner as a function of continuity in environmental gradient. Three major habitat types of the study area, were demarcated which could be compared with other studies where same techniques were used (Khan et al, 2016a;Khan et al, 2016b;Pruchniewicz, 2017). These studies assessed the influence of various environmental variables on plant species distribution and composition.…”
Section: Discussionmentioning
confidence: 99%
“…These studies assessed the influence of various environmental variables on plant species distribution and composition. To measure the effect of heavy metals and pollution on abundance and distribution of plants use of CANOCO Software could be compared with studies conducted by (Khan et al, 2012;Khan et al, 2013;Khan et al, 2016b;Bano et al, 2018) where they assessed the impact of topographic and edaphic factors on plant composition and distribution pattern.…”
Section: Discussionmentioning
confidence: 99%